2020
DOI: 10.21273/hortsci14760-19
|View full text |Cite
|
Sign up to set email alerts
|

GGE Biplot Analysis of Genotype-by-environment Interactions for Melon Fruit Yield and Quality Traits

Abstract: The stability of yield and quality traits in nine orange-fleshed melon (Cucumis melo L.) genotypes was studied over nine environments in south-central Texas (College Station, Uvalde, and Weslaco) over 3 years (2010, 2011, and 2012). Besides yield traits, fruit -quality components such as soluble solids content (SSC), β-carotene, and fruit firmness were also measured. Data were subjected to the combined analysis of variance and trait stability by GGE Biplot. The significant ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…In this study, none of the accessions were recorded to be adaptable and stable in the environments tested. [42]. This ability gives it an edge over the AMMI biplot analysis [43].…”
Section: Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, none of the accessions were recorded to be adaptable and stable in the environments tested. [42]. This ability gives it an edge over the AMMI biplot analysis [43].…”
Section: Stability Analysismentioning
confidence: 99%
“…GGE biplot allows environment evaluation based on the discriminating ability and representativeness of the GGE view [42]. This ability gives it an edge over the AMMI biplot analysis [43].…”
Section: Gge Biplot Analysismentioning
confidence: 99%
“…Although MET primarily focus on identifying superior genotypes for target environments, established breeding programs also apply MET to generate relevant information about tested environments (Gauch and Zobel, 1997;Yan et al, 2000;Yan and Kang, 2002;Laffont et al, 2013;Gauch, 2013;Yan, 2015Yan, , 2016. This analysis can be useful to identify mega-environments (ME) across a wider production area (Rakshit et al 2012;Nielsen and Vigil 2018;Dalló et al 2019;Sharma et al 2020;Ansarifard et al 2020) A common breeding approach for multinational commercial breeding programs is to cross elite germplasm adapted to diverse target environments (Cooper et al, 2014). Studies have demonstrated the potential advantages of utilizing this strategy in hybrid crops (Podlich and Cooper, 1998;Technow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The beta-carotene content levels in these parents were 6.56 and 0.15 µg g -1 , respectively, which are lower values than those observed in the present work. It is underlined that beta-carotene content is influenced by the genotype, the stage of fruit development and environmental conditions (Sharma et al, 2020;Singh et al, 2021). Clayberg (1992) checked epistasis between the genes gf and wf for the genotypic combinations (wf + _/gf + _) and (wf + _/gfgf ) to produce fruit with orange mesocarp, as well as for combinations (wfwf / gf + _) to produce fruit with white mesocarp, and the combination (wfwf/gfgf ) which is responsible for the green color.…”
Section: Resultsmentioning
confidence: 99%